The doctrine of party autonomy in international commercial arbitration: myth or reality (2015)
The increased preference for arbitration has buttressed the growing disenchantment for traditional adversary method of litigation. The foundation of every arbitration proceeding is the arbitration agreement. The parties’ agreement constitutes a contract to refer disputes, which have arisen or may arise in future between them to arbitration. The freedom of parties to consensually execute arbitration agreement is known as the principle of party autonomy. The principle provides a right for the parties to international commercial arbitration to choose applicable substantive law and these laws when chosen shall govern the contractual relationship of the parties. However, the pertinent questions have always been: Do parties actually have absolute freedom to determine the arbitration process? To what extent has this been achieved in the resolution of disputes having international concerns? And lastly, is party autonomy a myth or reality? These questions and many others have continued to provoke discussions in many fora on the applicability of party autonomy in international commercial arbitration. To find meaning to the above questions, this article analyses the principle of party autonomy. The ultimate aim of the article is to answer the question whether the practical application of the principle of party autonomy is indeed a myth or reality?